The Role of DsrC in Dissimilatory Sulfite Reduction - Preto, André Gonçalves Carvalho (2018)
Studies involving the human gastrointestinal microbiota and its metabolites have revealed the presence of sulfate-reducing bacteria (SRB) within the gut. These microorganisms have been implicated in inflammatory bowel diseases due to the toxic effects of sulfide, produced during dissimilatory sulfate reduction, leading to cell inflammation. The reduction of sulfite to sulfide is carried out by the dissimilatory sulfite reductase, DsrAB, and also involves the DsrC protein, which is a major protein in the cell and contains two conserved redox-active cysteines in a flexible C-terminal arm. The disulfide bond formed between these two conserved cysteines during sulfite reduction is believed to be reduced by several proteins that are related to the catalytic subunits of the heterodisulfide reductases (Hdr) of methanogens, namely HdrB and HdrD.